Local scale wave forecasting aiding harbor safety; A case study in Heraklion Port - Metheniti, Vassiliki; Parasyris, Antonios; Alexandrakis, George; Kozyrakis, Georgios; Kampanis, Nikolaos (Technical Annals, 2024)
With climate change intensifying wave hazards and storm surges, reliable wave forecasting is essential for harbor safety. This study presents a high-resolution SWAN wave model, specifically tailored for the Port of Heraklion, Greece’s third busiest passenger port, to enhance maritime safety and optimize ship scheduling (for entry, departure, and cargo handling) to support environmentally sustainable port operations. The model, dynamically downscaled to 50 m, is under a daily operational run cycle within a packaged application, and provides detailed forecasts of wave heights, crucial for planning cargo operations, optimizing ship disembarkation during adverse weather conditions, and ensuring safer navigation.